Functional ability of men aged 65 or more - Ilija Stijepić; Tamara Popović; Dragana Sredić-Cartes (Биомедицинска истраживања, 2019)
Introduction: Aging is a biological process leading to the decrease in functional ability which is defined as an ability to perform activities of daily living in a secure, independent and effective way. The aim of the study was to examine the functional ability of men aged ? 65 years as well as to determine the differences in functional ability in relation to the age of respondents. Methods: The study included 120 men aged ? 65 years from Banja Luka and Prijedor region. The patients were divided into four groups depending on their age. The Senior Fitness Test was used for functional ability evaluation. Results: The Senior Fitness Test showed a statistically significant difference between the group of patients aged 65-69 years and the group of respondents aged ?80 years in all of the tests except for strength tests. The subjects aged ?80 years had significantly poorer flexibility of the lower extremities compared to the subjects in the remaining three groups. The smallest statistical difference between the groups of different age structure was found in the parameters of upper extremity strength which progressively but negligibly declined with age. Six-minute walk test showed a statistically significant difference between the group of patients aged 65-69 years (430.42±60.94 m) and the group of respondents aged ?80 years (370.57±76.727 m; p= 0.003). Conclusion: Aging leads to the progressive decrease in both upper and lower extremity strength, as well as in flexibility and aerobic ability. Therefore, the lowest functional ability is found in the respondents aged ?80 years.
Keywords: functional ability; aging; strength; flexibility; aerobic endurance